Social policy and the capability approach : concepts, measurements and application / [edited by] Mara A. Yerkes, Jana Javornik, Anna Kurowska. - Yerkes, Mara A.; Javornik, Jana; Kurowska, Anna, 1980- (Policy Press shorts. Research., 2019)
This book explores the advantages of the capability approach and offers a way forward in addressing conceptual and empirical issues as they apply specifically to social policy research and practice.